Stability Analysis for Car Following Model Based on Control Theory - 孟祥佩 李志鹏 葛红霞 (Communications in theoretical physics, 2014)
Stability analysis is one of the key issues in car-following theory. The stability analysis with Lyapunov function for the two velocity difference car-following model （for short, TVDM） is conducted and the control method to suppress traffic congestion is introduced. Numerical simulations are given and results are consistent with the theoretical analysis.